Pembuatan kasur Ditinjau Dari KHES - Junaidi Harahap; Dame Siregar; Nurhotia harahap (IAIN Padangsidimpuan, 2021)
Muamalah is a rule that governs one’s relationship with other. In muamalah allah SWT makes rules sothat people help each other, exchange needs in all matters of interest of their lives, whether by of buying and selling, renting, farming, or other companies, both for their own benefit and for wefare general. In sosopan village, most of the residents are farmers, and some are entrepreneurs, tailor and others. The mattress tailor is one of the economic supports in this pandemic wich requires staying at home, the material used in sewing this matterss is cotten: in the process of sewing this matterss, the purity of the material is highly ecpected by the communityto produce good matterss stitches and are comfortable to wear. And every consumer or society who orders amatterss from a tailor is always accompanied by a contract that the mattress that the customer or customer wants is purely cotton. This is where there tens to be a practice that is not in accordance with what has been agreed the begining, where the matterss tailor sells his clothes mixed with the rest of the stitches of other clothes (paco-paco), there is always a mixture of leftovers from the sewing of clothes in the seams of the matterss, in the middle of the matterss is filled with paco-paco. This practice occurs because matterss maker want to take advantage of the result of their casual stitches, these matterss makers load the mixture (paco-paco) right in the middle of the matterss. Next matterss, without any agreement with the buyer. In terms of the price of a matterss that contains paco-paco, the price is the same as a pure cotton matterss. This type of research is a field research using a qualitative descriftive analysis method. The approach of this reseach is by means of observation, interviews, documentation based on the provisions of the applicable Syariah Economic Law Compilation, wich relates to the manufacture of mattersses in sosopan village, Sosopan District, Padang Lawas regency. The researchesrs examined were matterss makers, matterss buyer, religious leader and traditional figures